THE INFLUENCE OF FUN THINKERS BOOK MEDIA TOWARDS SCIENCE CONCEPTS UNDERSTANDING OF 5TH GRADE STUDENT ON MIN 3 CENTRAL LOMBOK IN 2020/2021 ACADEMIC YEAR - Imam Hamzan Wijaya; Ida Ermiana; Baiq Niswatul Khair (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
This study aims to determine the effect of the fun thinkers' book media on understanding the science concept of class V MIN 3 Lombok students in the middle of the 2020/2021 school year. This research is a quantitative research method with Quasi-Experimental Design type Nonequivalen Control Group Design. The population in this study were all students in class V while the sample was class VB as the experimental class and class VA as the control class. The instrument used was a test to measure conceptual understanding and observation to determine the feasibility of learning using the fun thinkers' book media. The post-test average score of the experimental class students was 73.15, the control class was 63.96. Post-test learning outcomes data were analyzed using non-parametric tests, the results obtained were Sig.2-tailed value <0.05 (0.012 <0.05) at the 95% confidence level. This shows that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that there is a difference in the mean value of the experimental class and the control class, it can be concluded that there is an effect of the fun thinkers' book media on the understanding of the science concept of class V MIN 3 students. Lombok in the middle of the 2020/2021 school year. The media fun thinkers book media can provide a better understanding of the concept, the researcher suggests the teacher use the fun thinkers' book media as an alternative in solving students' conceptual understanding.